Cardiovascular disorders in patients with combined course of obstructive sleep apnea and gastroesophageal reflux diseaseCardiovascular disorders in patients with combined course of obstructive sleep apnea and gastroesophageal reflux disease - Krivenko, Vitaly; Svitlytska, Oksana (ScienceRise: Medical Science, 2019)
The aim: to investigate cardiovascular disorders in patients with combined obstructive sleep apnea (OSA) and gastroesophageal reflux disease (GERD) flow. Materials and methods: 165 patients aged 48 (36; 58) years were divided into four groups: I – 31 patients with GERD, II – 32 patients with OSA, III – 72 patients with comorbid OSA and GERD, control group – 30 practically healthy persons. All patients underwent: cardiorespiratory monitoring, ECG dispersion mapping (DM), daily ECG monitoring, echocardioscopy. Results: index “Myocardium” in group III according to DM ECG was by +14 % higher than in group II (p<0,05). Analysis of heart rate variability revealed in patients of group III the growth of SDNNi component by 1,6 times (p<0,05), RMSSD by 1,71 times, pNN50 – by 4,49 times compared with parameters in the control group (p<0,05 ). The HF component in group III exceeded the indicators in group I by 1.87 times, and the parameter LF was higher than in group II by +20,5 % (p<0,05). In group III, the TR component increased in 2,4 times compared with the control group (p<0,05). In patients of group III, every fourth has a daily profile of "night peaker", and every second – has a "non-dipper". The E/A ratio according to echocardioscopy in group III is less than – 18 % in group II (p<0,05). According to the results of ROC analysis, the index “Myocardium” is >18,28 % as a prognostic marker of cardiovascular disorders im patients with OSA and GERD combined flow. Conclusions: In patients with comorbid OSA and GERD revealed the most significant disorders of the cardiovascular system. In order to determine the cardiovascular disorders treatment effectiveness in patients with OSA and GERD, it is advisable to conduct dynamic monitoring of heart rate variability and echocardiography parameters